The Dietary Fructose:Vitamin C Intake Ratio Is Associated with Hyperuricemia in African-American Adults. Issue 3 (12th March 2018) - Zheng, Zihe; Harman, Jane L; Coresh, Josef; Köttgen, Anna; McAdams-DeMarco, Mara A; Correa, Adolfo; Young, Bessie A; Katz, Ronit; Rebholz, Casey M
Abstract: Background: A high fructose intake has been shown to be associated with increased serum urate concentration, whereas ascorbate (vitamin C) may lower serum urate by competing with urate for renal reabsorption. Objective: We assessed the combined association, as the fructose:vitamin C intake ratio, and the separate associations of dietary fructose and vitamin C intakes on prevalent hyperuricemia. Methods: We conducted cross-sectional analyses of dietary intakes of fructose and vitamin C and serum urate concentrations among Jackson Heart Study participants, a cohort of African Americans in Jackson, Mississippi, aged 21–91 y. In the analytic sample ( n  = 4576), multivariable logistic regression was used to examine the separate associations of dietary intakes of fructose and vitamin C and the fructose:vitamin C intake ratio with prevalent hyperuricemia (serum urate ≥7 mg/dL), after adjusting for age, sex, smoking, waist circumference, systolic blood pressure, estimated glomerular filtration rate, diuretic medication use, vitamin C supplement use, total energy intake, alcohol consumption, and dietary intake of animal protein. Analyses for individual dietary factors (vitamin C, fructose) were adjusted for the other dietary factor. Results: In the fully adjusted model, there were 17% greater odds of hyperuricemia associated with a doubling of the fructose:vitamin C intake ratio (OR: 1.17; 95% CI: 1.08, 1.28), 20% greater odds associated with a doubling of fructose intake (OR: 1.20; 95% CI: 1.08, 1.34), and 13% lower odds associated with a doubling of vitamin C intake (OR: 0.87; 95% CI: 0.78, 0.97). Dietary fructose and the fructose:vitamin C intake ratio were more strongly associated with hyperuricemia among men than women ( P -interaction ≤ 0.04). Conclusion: Dietary intakes of fructose and vitamin C are associated with prevalent hyperuricemia in a community-based population of African Americans.